2015
DOI: 10.1186/s12984-015-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Haptic wearables as sensory replacement, sensory augmentation and trainer – a review

Abstract: Sensory impairments decrease quality of life and can slow or hinder rehabilitation. Small, computationally powerful electronics have enabled the recent development of wearable systems aimed to improve function for individuals with sensory impairments. The purpose of this review is to synthesize current haptic wearable research for clinical applications involving sensory impairments. We define haptic wearables as untethered, ungrounded body worn devices that interact with skin directly or through clothing and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(135 citation statements)
references
References 146 publications
2
131
0
2
Order By: Relevance
“…We have witnessed the proliferation of wearable medical systems which have been paving the way towards pervasive and personalized healthcare [8,9,10,11,12,13].…”
Section: Related Workmentioning
confidence: 99%
“…We have witnessed the proliferation of wearable medical systems which have been paving the way towards pervasive and personalized healthcare [8,9,10,11,12,13].…”
Section: Related Workmentioning
confidence: 99%
“…Looking at the state-of-the-art, it is possible to observe a number of strategies for stimulus delivery through wearable systems, specifically developed to generate vibrations [4], apply forces [11], stimulate skin using pin-arrays [12] or using electrocutaneous feedback [13], and considering different body locations for stimulus application, such as arm [7,14], foot [15], finger [5,16], among the others; the interested reader may refer to references [16,17] (for a review of these topics see Figure 1). [5,16,18]; wrist [19,21]; arm and forearm [14,20,22,23]; tongue and mouth [24][25][26]; head [27]; torso, trunk and shoulders [28][29][30]; leg [31,32]; foot [15,33].…”
Section: Wearable Haptic Systems: Technologies and Main Characteristicsmentioning
confidence: 99%
“…Each of these strategies comes with pros and cons, which must be considered in light of the applications that WHS are designed for, such as rehabilitation, assistive robotics, guidance, among others-the interested reader can refer to reference [17] for further details. From a physiological point of view, different stimulation modes target the different mechanoreceptors of human skin, of which the main characteristics and response typologies are summarized in Table 2 (note that all contribute to guarantee stable precision grasp and manipulation [37,38])-for an exhaustive description of mechanoreceptor characteristics, the reader can refer to references [37][38][39][40].…”
Section: Location Devicesmentioning
confidence: 99%
“…Aside from haptics, many wearable navigation assistance devices have been proposed for VI individuals (reviews of which may be found in [7] [29]). These can resemble instrumented and actuated jackets, corsets and motorbike helmets.…”
Section: Related Workmentioning
confidence: 99%